Numerical simulation of soda ash drying process in pneumatic drying system with industrial scale - Edisa Papraćanin; Nisad Avdić; Abdel Đozić; Ervin Karić (Journal of Engineering & Processing Management, 2021)
In this paper a mathematical model for the soda ash drying process in a pneumatic dryer was presented. The model presents a macroscopic aspect of the drying process, for a two-phase, gas-solid system. The model is based on mass and heat transfer between the gas phase and the particle, movement of air and particles through the system, and geometric characteristics of the drying system (fan, air heater, pneumatic dryer, and cyclone). The effects of the process parameters, such as airflow, inlet air temperature, and relative humidity, temperature at the inlet of the dryer, etc., have been studied by solving the model. Also, the model was tested for different values of the capacity of wet soda and different values of the operating parameters of the heating medium. The model was implemented in MATLAB and solved with a nonlinear equations solver. Data obtained by the model were compared with industrial pneumatic dryer data for drying wet soda ash particles with good agreement.
Keywords: industrial scale; mathematical model; pneumatic dryer; soda ash; numerical simulation